2015
DOI: 10.1002/jcc.24042
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced stability of the model mini‐protein in amino acid ionic liquids and their aqueous solutions

Abstract: Abstract. Using molecular dynamics simulations, the structure of model mini-protein was thoroughly characterized in the imidazolium-based amino acid ionic liquids and their aqueous solutions. We report that the mini-protein is more stable when AAIL is added as a cosolvent.Complete substitution of water by organic cations and anions further results in hindered conformational flexibility of the mini-protein. This observation suggests that AAILs are able to defend proteins from thermally induced denaturation. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 37 publications
(79 reference statements)
1
22
0
1
Order By: Relevance
“…Amino acid-based ILs are another promising class of biocompatible ILs that have received some interest in recent years (Chevrot et al 2015;Guncheva et al 2015;Sankaranarayanan et al 2012;Tarannum et al 2018). Amino acids have been mostly incorporated as anions, especially with imidazolium or choline cations to produce a biocompatible or Bgreen^IL.…”
Section: Choline-based Ilsmentioning
confidence: 99%
“…Amino acid-based ILs are another promising class of biocompatible ILs that have received some interest in recent years (Chevrot et al 2015;Guncheva et al 2015;Sankaranarayanan et al 2012;Tarannum et al 2018). Amino acids have been mostly incorporated as anions, especially with imidazolium or choline cations to produce a biocompatible or Bgreen^IL.…”
Section: Choline-based Ilsmentioning
confidence: 99%
“…RMSD is not only the function of solvent transport properties, but also, and to a larger extent, it is depended on specic chemical interactions between the solute molecule and solvent system. 42 Fig . 7D shows the difference between average RMSD of naringin-DMSO and naringin-water versus mole fraction of DMSO.…”
Section: View Article Onlinementioning
confidence: 99%
“…However, Chaban and co-workers (Chevrot et al 2015 ) showed that the radius of gyration does not increase in ionic liquids with amino acid-based anions during the simulation period of 10 ns which may not be long enough to monitor the unfolding process due to the high viscosity of these ionic liquids. Interestingly, Shao ( 2013 ) reported that r g y r of the B domain of protein A from Staphylococcus aureus actually decreased with increasing [C 4 mim]Cl content of the aqueous solution.…”
Section: Large Flexible Proteinsmentioning
confidence: 99%